(untitled) (Carte Romanze, 2023)
ABSTRACT: The article studies the original interpolations in manuscript B (Venice, Museo Correr 1493) peculiar version of the Roman d’Alexandre: a deep analysis has never been tried despite this codex interest in the tradition of the Roman d’Alexandre. It shows that this text is linked with other works in the matière of Alexander, such as the Historia de Preliis¸ the Libro de Alexandre and the Alexanderlied, but also some influences that have been hard to track: Christian apocryphal literature and Hebrew legends on Salomon, among the many. KEY WORDS: Roman d’Alexandre, interpolations, Alexander the Great, manuscript tradition, Babylon.